RETRACTED: Mammalian STE20-Like Kinase 2 Promotes Lipopolysaccharides-Mediated Cardiomyocyte Inflammation and Apoptosis by Enhancing Mitochondrial Fission - Tian, Yanan; Song, Haijiu; Qin, Wei; Ding, Zhenjiang; Zhang, Ying; Shan, Weichao; Jin, Dapeng (Frontiers in Physiology, 2020)
In this study, we analyzed the role of mammalian STE20-like protein kinase 2 (Mst2), a serine-threonine protein kinase, in Lipopolysaccharides (LPS)-mediated inflammation and apoptosis in the H9C2 cardiomyocytes. Mst2 mRNA and protein levels were significantly upregulated in the LPS-treated H9C2 cardiomyocytes. LPS treatment induced expression of IL-2, IL-8, and MMP9 mRNA and proteins in the H9C2 cardiomyocytes, and this was accompanied by increased caspase-3/9 mediating H9C2 cardiomyocyte apoptosis. LPS treatment also increased mitochondrial reactive oxygen species (ROS) and the levels of antioxidant enzymes, such as GSH, SOD, and GPX, in the H9C2 cardiomyocytes. The LPS-treated H9C2 cardiomyocytes showed lower cellular ATP levels and mitochondrial state-3/4 respiration but increased mitochondrial fragmentation, including upregulation of the mitochondrial fission genes Drp1, Mff, and Fis1. LPS-induced inflammation, mitochondrial ROS, mitochondrial fission, and apoptosis were all significantly suppressed by pre-treating the H9C2 cardiomyocytes with the Mst2 inhibitor, XMU-MP1. However, the beneficial effects of Mst2 inhibition by XMU-MP1 were abolished by carbonyl cyanide-4-(trifluoromethoxy) phenylhydrazone (FCCP), a potent activator of mitochondrial fission. These findings demonstrate that Mst2 mediates LPS-induced cardiomyocyte inflammation and apoptosis by increasing mitochondrial fission.